Efficacy, Safety, and Pharmacokinetics of Sugammadex for the Reversal of Rocuronium-induced Neuromuscular Blockade in Elderly Patients - McDonagh, David L.; Benedict, Patrick E.; Kovac, Anthony L.; Drover, David R.; Brister, Neil W.; Morte, Jovino B.; Monk, Terri G. (Anesthesiology (Philadelphia), 2011)
The management of elderly patients can be challenging for anesthesiologists for many reasons, including altered pharmacokinetics and dynamics. This study compared the efficacy, safety, and pharmacokinetics of sugammadex for moderate rocuronium-induced neuromuscular blockade reversal in adult (aged 18-64 yr) versus elderly adult (aged 65 yr or older) patients. This phase 3a, multicenter, parallel-group, comparative, open-label study enrolled 162 patients aged 18 yr and older, American Society of Anesthesiologists class 1-3, scheduled for surgery with general anesthesia and requiring neuromuscular blockade. After anesthesia induction, patients received rocuronium, 0.6 mg/kg, before tracheal intubation, with maintenance doses of 0.15 mg/kg as required. At the end of surgery, patients received sugammadex, 2.0 mg/kg, at reappearance of the second twitch of the train-of-four (TOF) for reversal. The primary efficacy variable was time from sugammadex administration to recovery of the TOF ratio to 0.9 or greater. Pharmacokinetics and safety were also evaluated. Overall, 150 patients were treated and had at least one postbaseline efficacy assessment; 48 were aged 18-64 yr (adult), 62 were aged 65-74 yr (elderly), and 40 were aged 75 yr or older (old-elderly). The geometric mean time (95% confidence interval) from sugammadex administration to recovery of the TOF ratio to 0.9 increased with age, from 2.3 (2.0-2.6) min (adults) to 2.9 (2.7-3.2) min (elderly/old-elderly groups combined). Recovery of the TOF ratio to 0.9 was estimated to be 0.7 min faster in adults compared with patients aged 65 yr or older (P = 0.022). Sugammadex was well tolerated by all patients. Sugammadex facilitates rapid reversal from moderate rocuronium-induced neuromuscular blockade in adults of all ages.